MORPHOMETRIC ANALYSIS OF RED SNAKE FRUIT (Salacca edulis) BASED ON DIFFERENT GROWTH SPOT ALTITUDE - Alwi Smith; Rufiaty Simal; Kristin Sangur (EDU SCIENCES JOURNAL, 2023)
In Maluku province, especially West Seram Regency (SBB) Taniwel district, has been found the snake fruit with thick fruit with dark yellow color and red dispersion, named salak merah. Buria village and Riring village are samples of breeding central red snake fruit at different altitude that allows different morphology characteristics on red snake fruit, especially on its fruit. the purpose of this research is to know the morphometrics of red snake fruit at lower altitude (Buria village) and higher altitudes (Riring village). This research is a laboratory research type with the only object being red snake fruit taken with purposive sampling. Data were analyzed descriptively. The research shows that the morphometric of red snake fruit from Buria village for length fruit parameter, fruit diameter, middle thickness, skin thickness, and fruit weight in the range of 5.33 cm, 4.66 cm, 1.72 cm, 0.1 cm, and 52.89 gr. While the morphometric of red snake fruit from Riring village was in the range of 5.15 cm, 4.45 cm, 1.47 cm, 0,1 cm, and 46.51 gr. The morphometric value of red snake fruit of Buria village is higher compared to the morphometric value of red snake fruit from Riring village. Therefore, we can conclude that the difference in the altitude of the growth spot gives a real significant difference in the morphometric value of red snake fruit, where the higher the altitude at the plant grows, the lower the morphometric value of the plant. This research is only limited to the fruit morphometric, in hope that there will be another progression on other morphometric parameters, like a leaf, stem, and flower, in addition to its environmental chemical and physical factors that giving significant influence towards the morphometric value of red snake fruit in Taniwel district, West Seram Regency (SBB).